Tumor Volume Useful Beyond Classic Criteria in Selecting Larynx Cancers For Preservation Therapy. (13th November 2019) - Sharrett, Jonathan M.; Ward, Matthew C.; Murray, Eric; Scharpf, Joseph; Lamarre, Eric D.; Prendes, Brandon L.; Lorenz, Robert R.; Burkey, Brian B.; Koyfman, Shlomo A.; Woody, Neil M.; Greskovich, John F.; Adelstein, David J.; et al.
Abstract : Objective: To investigate the association between tumor volume and locoregional failure (LRF) after concurrent chemoradiation (CCRT) for locally advanced larynx cancer (LC). Methods: This is a retrospective cohort study from 2009 to 2014 identified from an institutional review board–approved registry. Fifty‐nine of 68 patients with locally advanced larynx cancer treated with definitive CCRT who had available imaging for review were identified. The main endpoint to be assessed was the association between gross tumor volumes (GTV; T = total, P = primary, N = nodal) and LRF. Receiver operative characteristic (ROC) curves were used to investigate diagnostic accuracy. Results: Twenty LRFs were observed, resulting in a 2‐year LRF rate of 39% (95% CI, 23–52%). On UVA, the GTV‐T ( P = .01), GTV‐P ( P = .05), and GTV‐N ( P = .04) were statistically significant predictors of LRF. Furthermore, age, smoking status, N‐stage, larynx subsite, and tracheostomy/feeding tube dependence were potentially associated with LRF ( P < .3), whereas T‐stage (T3–4 vs. T2) was not (HR 1.05, 95% CI, 0.38–2.91, P = .92). In the multivariable model, GTV‐P (HR 1.022, 95% CI, 0.999–1.046, P = .07) and GTV‐N (HR 1.053, 95% CI, 1.0004–1.108, P = .05) were the two most impactful covariates on the model's R 2 . ROC analysis suggested an optimal cut point of 12 cc in the GTV‐T. The 2‐year LRF for GTV‐T > 12 cc was 64.2% and ≤ 12 cc was 16.4%, P = .006. Conclusion: GTV is associated with LRF after definitive CCRT for LC. Patients with bulky primary and/or nodal tumors may be better served with upfront surgical resection regardless of T‐stage. Further investigation into the safety of larynx preservation for low‐volume T4 tumors can be considered. Level of Evidence: 4 Laryngoscope, 130:2372–2377, 2020